Peta Maqashid Asy-Syariah dalam Hermeneutika Kontekstual Abid Al Jabiri - Barir, Muhammad (Yayasan Al-Aziziyah Tlogoagung Kedungadem Bojonegoro, 2023)
AbstractThis research focuses on the views of Abid Al Jabiri, a 20th century scholar who reconstructed the concept of contextualizing the Qur'an as a holy book that is tied to historical reality. The use of